Effect-Directed, Chemical and Taxonomic Profiling of Peppermint Proprietary Varieties and Corresponding Leaf Extracts - Antonio M. Inarejos-Garcia; Julia Heil; Patricia Martorell; Beatriz Álvarez; Silvia Llopis; Ines Helbig; Jie Liu; Bryon Quebbeman; Tim Nemeth; Deven Holmgren; Gertrud E. Morlock (MDPI AG, 2023)
During the development of novel, standardized peppermint extracts targeting functional applications, it is critical to adequately characterize raw material plant sources to assure quality and consistency of the end-product. This study aimed to characterize existing and proprietary, newly bred varieties of peppermint and their corresponding aqueous extract products. Taxonomy was confirmed through genetic authenticity assessment. Non-target effect-directed profiling was developed using high-performance thin-layer chromatography-multi-imaging-effect-directed assays (HPTLC-UV/Vis/FLD-EDA). Results demonstrated substantial differences in compounds associated with functional attributes, notably antioxidant potential, between the peppermint samples. Further chemical analysis by high-performance liquid chromatography-photodiode array/mass spectrometry detection (HPLC-PDA/MS) and headspace solid-phase microextraction-gas chromatography-flame ionization/MS detection (headspace SPME-GC-FID/MS) confirmed compositional differences. A broad variability in the contents of flavonoids and volatiles was observed. The peppermint samples were further screened for their antioxidant potential using the Caenorhabditis elegans model, and the results indicated concordance with observed content differences of the identified functional compounds. These results documented variability among raw materials of peppermint leaves, which can yield highly variable extract products that may result in differing effects on functional targets in vivo. Hence, product standardization via effect-directed profiles is proposed as an appropriate tool.